The relationship between the manifestations of mobbing and reactions of mobbing victims - Lidia Grzesiuk; Agnieszka Szymańska; Justyna Jastrzębska; Małgorzata Rutkowska (Nofer Institute of Occupational Medicine, 2022)
Background The study concerned workplace mobbing, a phenomenon affecting about 3-20% of the Polish population. The aim of the article is to distinguish the manifestations of mobbing, to study the coexistence of mobbing manifestations, and to search for the relationships between the symptoms of mobbing, reactions to mobbing and methods of dealing with mobbing used by victims. Material and Methods Information on the above variables was obtained using a questionnaire on mobbing, risk factors, and responses to mobbing. The questionnaire was completed by 781 people (women: 66%, men: 34%). The average age of the respondents was 29 years. The current statistical analysis included: distinguishing the manifestations of mobbing by means of a confirmatory factor analysis, studying the coexistence of mobbing manifestations by means of a cluster analysis, and detecting the relationships between mobbing manifestations, reactions to mobbing and ways of dealing with it based on the system of structural equations. Results The results of the research revealed 3 categories of relationships: a co-occurrence of mobbing manifestations, a relationship of mobbing manifestations with reactions to mobbing, and a relationship of mobbing reactions with methods of dealing with mobbing. Conclusions Mobbing was found in 22% of the examined group. The study revealed the existence of 5 clusters of mobbing manifestations (i.e., subgroups of respondents characterized by experiencing at least 1 of the mobbing manifestations). In the most numerous clusters in which the symptoms of mobbing were diagnosed, unfriendly working conditions prevailed. In the context of mobbing, people were found to more often react with passivity or with using interpersonal coping methods. However, they rarely turned to institutions for help or used aggression against the mobber. Med Pr. 2022;73(1):1-12